Effects of Preoperative Embolization on Spetzler–Martin Grade I and II Arteriovenous Malformations: A Propensity-Adjusted Analysis. Issue 1 (January 2022) - Catapano, Joshua S.; Srinivasan, Visish M.; Rumalla, Kavelin; Koester, Stefan W.; Kimata, Anna R.; Ma, Kevin L.; Labib, Mohamed A.; Baranoski, Jacob F.; Cole, Tyler S.; Rutledge, Caleb; Ducruet, Andrew F.; Albuquerque, Felipe C.; et al.
Abstract : BACKGROUND: Cerebral arteriovenous malformations (AVMs) with low Spetzler–Martin grades (I and II) are associated with good neurological outcomes after microsurgical resection; however, the use of preoperative embolization for these lesions is controversial. OBJECTIVE: To compare the neurological outcomes of preoperative embolization with no embolization in patients with low-grade AVMs. METHODS: Patients with a Spetzler–Martin grade I or II AVM who underwent microsurgical resection during January 1, 1997, through December 31, 2019, were analyzed. Patients undergoing preoperative embolization were compared with patients not undergoing embolization. A propensity score was constructed from baseline characteristics and used to match intervention (embolization) and control (nonembolization) groups in a 1:1 ratio. The primary outcome was poor neurological status on last follow-up examination, defined as a modified Rankin Scale score >2 and a modified Rankin Scale score worse at follow-up than at the preoperative examination. RESULTS: Of the 603 patients analyzed, 310 (51.4%) underwent preoperative embolization and 293 (48.6%) did not. Patients in the embolization cohort compared with those in the nonembolization cohort had a higher percentage of Spetzler–Martin grade II AVMs (71.6% vs 52.6%, P < .001) and a lower percentage of hemorrhage (41% vs 55%, P = .001). After propensity score matching, no differences were found between paired cohorts (each N = 203) for baseline characteristics with a significant reduction in absolute standardized mean differences. No significant differences were found in primary outcomes between treatment groups in the matched or unmatched cohorts. CONCLUSION: Preoperative embolization of low-grade Spetzler–Martin AVMs is not associated with improved neurological outcomes after microsurgical resection.